Hepatoprotective Activity Test of Longan Leaf Methanol Extract (Euphoria Longan (L.) Steud.) Against Paracetamol-Induced SGOT and SGPT Liver Levels of Male White Rats - Megahati S, Ruth Rize Paas; Mitra FEBTA (RADINKA JOURNAL OF HEALTH SCIENCE, 2024)
Euphoria longan (L.) Steud. or longan leaves, is a plant that contains secondary metabolites, flavonoids which have the potential as a source of antioxidants that can prevent liver damage due to the use of toxic doses of paracetamol. This study aims to determine the presence of hepatoprotective activity of methanol extract of longan leaves in reducing levels of SGPT and SGOT in the livers of paracetamol-induced male white rats. This study used 24 male white rats which were divided into 6 treatment groups, namely group I as normal control, group II as negative control who were given paracetamol, group III as positive control who were given Legalon ® dose of 272.15 mg/kg, groups IV, V, and VI were given longan leaf methanol extract at doses of 386.125 mg/kg, 772.25 mg/kg, and 1544.5 mg/kg. On day 7, all groups except the normal group were induced by paracetamol at a dose of 1000 mg/kg BW. Data on SGPT and SGOT levels were analyzed using a one-way ANOVA test and followed by a Tukey test. The results of the statistical analysis obtained showed that the methanol extract of longan leaves in the dose 3 group was not significantly different from the positive control (p>0.05), which means that dose 3 had the best hepatoprotective activity in reducing SGPT and SGOT levels in the liver of paracetamol-induced rats compared to with doses 1 and 2. Giving dose III (1544.5 mg/kg BW) has the best hepatoprotective activity because it is comparable to the positive control group given Legalon® at a dose of 272.15 mg/kg BW.